Covid-19, leukemia, and secondary malignancies of the skin – is there a connection: a case report and literature analysis - Bogomolets, Olga; Rojczyk, Ewa; Hryshchenko, Roman; Bogomolets, Catherine; Berezkin, Oleksandr (Frontiers in Oncology, 2023)
We report the case of a patient who was diagnosed with two melanomas and one skin cancer within two years. Of particular interest was the fact, that at the time these tumors were diagnosed, the patient was already suffering from chronic myeloid leukemia, which developed three months after recovering from Covid-19. From the time of leukemia occurrence, the patient has been taking the tyrosine kinase inhibitor (TKI) -Gleevec. Thus, we took into the account the possibile effect of Gleevec administration on the risk of skin tumor appearance. It was also important to analyze the impact of the SARS-CoV-2 virus and chronic myeloid leukemia on the risk of secondary malignancies. According to so far published data, the direct relationship between Gleevec treatment and the occurrence of skin cancers cannot be proved. However, literature data indicate a direct and indirect relationship between SARS-CoV-2 infection and an increased incidence of carcinogenesis.